2016
DOI: 10.1371/journal.pbio.1002511
|View full text |Cite
|
Sign up to set email alerts
|

Role of Mitochondrial Dynamics in Neuronal Development: Mechanism for Wolfram Syndrome

Abstract: Deficiency of the protein Wolfram syndrome 1 (WFS1) is associated with multiple neurological and psychiatric abnormalities similar to those observed in pathologies showing alterations in mitochondrial dynamics. The aim of this study was to examine the hypothesis that WFS1 deficiency affects neuronal function via mitochondrial abnormalities. We show that down-regulation of WFS1 in neurons leads to dramatic changes in mitochondrial dynamics (inhibited mitochondrial fusion, altered mitochondrial trafficking, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
165
3
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 113 publications
(182 citation statements)
references
References 40 publications
10
165
3
3
Order By: Relevance
“…Cherra et al () demonstrated that excess cytosolic Ca 2+ is associated with profound mitophagy and that restoring Ca 2+ homeostasis through Ca 2+ chelation or inhibition of voltage‐gated Ca 2+ channels was sufficient to prevent the mutant LRRK2 phenotype related to Parkinson disease. We have recently demonstrated that increased cytosolic Ca 2+ levels are associated with profound mitophagy in Wolfram syndrome 1‐deficient neurons (Cagalinec et al , ). Current findings allow us to speculate that Miro proteins may also play a significant role in that process.…”
Section: Discussionmentioning
confidence: 99%
“…Cherra et al () demonstrated that excess cytosolic Ca 2+ is associated with profound mitophagy and that restoring Ca 2+ homeostasis through Ca 2+ chelation or inhibition of voltage‐gated Ca 2+ channels was sufficient to prevent the mutant LRRK2 phenotype related to Parkinson disease. We have recently demonstrated that increased cytosolic Ca 2+ levels are associated with profound mitophagy in Wolfram syndrome 1‐deficient neurons (Cagalinec et al , ). Current findings allow us to speculate that Miro proteins may also play a significant role in that process.…”
Section: Discussionmentioning
confidence: 99%
“…WS, caused by a deficiency in the Wolfram syndrome 1 (WFS1) protein, is a genetic disorder that impacts early brain development and displays neurological abnormalities similar to pathologies showing alterations in mitochondrial dynamics (Barrett et al, 1997;Kanki and Klionsky, 2009;Hershey et al, 2012;Ross-Cisneros et al, 2013). A recent study has now revealed that down-regulation of WFS1 causes severe changes in mitochondrial dynamics and delays neuronal development (Cagalinec et al, 2016). Lastly, studies in postmortem brains of schizophrenia subjects have shown a reduction in the number and size of mitochondria (Uranova et al, 2001).…”
Section: Disruption Of Mitochondrial Dynamics and Neurodevelopmental mentioning
confidence: 99%
“…These dynamical processes respond to cellular conditions to affect morphology and function. There is no formula known that connects form and function of mitochondria, yet distortion of mitochondrial morphology as well as ultrastructure is associated with many neurodegenerative disorders (Bindoff et al, 1991; Cagalinec et al, 2016; Corrado et al, 2012; Knott et al, 2008; Rugarli and Langer, 2012; Schon and Przedborski, 2011). At the level of whole organelles, the predominate theory is that when bioenergetic needs are high, for example during starvation, mitochondria are more tubular in connected networks, thereby preventing the degradation of small mitochondria by mitophagy (Gomes et al, 2011a; Rambold et al, 2011).…”
Section: Many Events and Conditions Influence Mitochondrial Dynamicsmentioning
confidence: 99%
“…Thus, mitochondrial morphology is intertwined with mitochondrial function, but most of the details are not yet known (Benard and Rossignol, 2008; Bindoff et al, 1991; Guillery et al, 2008; Wai and Langer, 2016). However, interest in this direction is spawned by the alterations in mitochondrial structure and function associated with aging, cancer, heart disease and a growing number of neurological disorders including epilepsy, stroke, Wolfram syndrome, Alzheimer’s disease, Parkinson’s disease, and Huntington’s disease (Archer, 2013; Cagalinec et al, 2016; Corrado et al, 2012; Knott et al, 2008; Lee et al, 2016b; Rugarli and Langer, 2012; Schon and Przedborski, 2011; Vafai and Mootha, 2012). Much less is known about ultrastructural morphology and dynamics of mitochondrial inner membrane cristae despite being disrupted in neurodegenerative and other disease states.…”
Section: Introductionmentioning
confidence: 99%